Using diluted winery effluent for irrigation of Vitis Vinifera. Cv. Cabernet Saugvignon and the impact thereof on soil properties with special reference to selected grapevine responses. - Howell, Carolyn Louise (Stellenbosch : Stellenbosch University, 2016)
Thesis (PhD)--Stellenbosch University, 2016.